1981
DOI: 10.1029/ja086ia07p05643
|View full text |Cite
|
Sign up to set email alerts
|

Charged particle behavior in low‐frequency geomagnetic pulsations 1. Transverse waves

Abstract: The behavior of charged particles in low-frequency geomagnetic pulsations is examined with particular emphasis on what a spacecraft-borne detector would observe. We concentrate on the effects of purely transverse electromagnetic signals. The time scale of a particle's motion relative to the wave period is shown to determine the nature of its response. For low-energy particles, the acceleration in the last gyroperiod before detection is what matters. At higher energies, what has occurred over recent bounce and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
376
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(400 citation statements)
references
References 36 publications
15
376
1
3
Order By: Relevance
“…In situ observations of drift-bounce-resonance between energetic electrons and ULF waves following IP shocks have been reported by (Zong et al 2007(Zong et al , 2009aTan et al 2004Tan et al , 2011. As mentioned earlier, this is possible because of the comparable periods of energetic particle drift motion and ULF oscillations (e.g., Southwood and Kivelson 1981;Takahashi et al 1985Takahashi et al , 1990Takahashi et al , 1992Hudson et al 2008;Zong et al 2007Zong et al , 2009a. Drift-resonance with poloidal mode ULF waves (Zong et al 2009a, b) and compressional waves (Tan et al 2011) induced by IP shock impact is associated with fast electron acceleration and even the formation of new radiation belts .…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…In situ observations of drift-bounce-resonance between energetic electrons and ULF waves following IP shocks have been reported by (Zong et al 2007(Zong et al , 2009aTan et al 2004Tan et al , 2011. As mentioned earlier, this is possible because of the comparable periods of energetic particle drift motion and ULF oscillations (e.g., Southwood and Kivelson 1981;Takahashi et al 1985Takahashi et al , 1990Takahashi et al , 1992Hudson et al 2008;Zong et al 2007Zong et al , 2009a. Drift-resonance with poloidal mode ULF waves (Zong et al 2009a, b) and compressional waves (Tan et al 2011) induced by IP shock impact is associated with fast electron acceleration and even the formation of new radiation belts .…”
Section: Introductionmentioning
confidence: 82%
“…The other possible scenario whereby poloidal ULF waves can be excited is through drift-bounce resonance (Southwood and Kivelson 1981). suggested that energetic ring current ions can excite poloidal ULF waves of Schematic showing how a pressure enhancement associated with an IP shock drives reconfiguration in the nightside magnetosphere.…”
Section: Ulf Waves Driven By the Transient Foreshock Phenomenamentioning
confidence: 99%
See 2 more Smart Citations
“…the pulsations are antisymmetric with respect to the.equator (second harmonic). Southwood and Kivelson (1981) showed mathematically that in the case where a signal electric field is antisymmetric about the equator, resonance is possible only for particles that detect odd harmonics of the bounce frequency. Therefore, we set N=±1 and the values for m derived using the finite gradient techniques above as a function of radius.…”
Section: Drift Bounce Resonance Testmentioning
confidence: 99%